TINJAUAN YURIDIS TERHADAP PELAKSANAAN SISTEM ELECTRONIC TRAFFIC LAW ENFORCEMENT (E-TLE) BERDASARKAN UNDANG UNDANG NOMOR 22 TAHUN 2009 TENTANG LALU LINTAS DAN ANGKUTAN JALAN - David, Andy (Universitas 17 Agustus 1945 Samarinda, 2025)
ABSTRACTThe development of science and technology that occurs today brings significant changes in every activity of human life, so that the police are encouraged to develop an information system supported by a network-based software, namely the Electronic Traffic Law Enforcement (E-TLE) system or commonly called electronic ticketing. However, after the implementation of the Electronic Traffic Law Enforcement (E-TLE) system, continuous improvements are still being made so that its implementation among the community is not optimal. The problem in this study is how to find out the regulations for the implementation of the Electronic Traffic Law Enforcement (E-TLE) system and how to find out the procedures for implementing the Electronic Traffic Law Enforcement (E-TLE) system for resolving traffic violations. The approach method used in this study is the Normative Juridical approach, which inductively researchers go directly to the research object to observe and study the legal reality in the field. The problem approach examines primary data as the main data in addition to also using secondary data. This is so that the data in the study is more accurate because it comes directly from the object and subject. Based on the research results, it is described that the regulation of the implementation of Electronic Traffic Law Enforcement (E-TLE) is seen from Law Number 22 of 2009 concerning Traffic and Road Transportation, in general in Article 272 paragraph (1) and paragraph (2), Government Regulation Number 80 of 2012, and Law Number 19 of 2016 Article 1 number (1). The procedure for implementing the Electronic Traffic Law Enforcement (E-TLE) system based on Article (1) paragraph (2) of Supreme Court Regulation Number 12 of 2016 has 10 stages, namely: installation of Closed Circuit Television (CCTV); recording of violator data; SRC (Smart Regident Center) identity; sending letters; delivery of letters; confirmation; clarification; issuance of traffic tickets and BRIVA codes; blocking of vehicle registration certificates; and payment of traffic fines. The Electronic Traffic Law Enforcement (E-TLE) system so far still has obstacles in its utilization, especially in terms of facilities and infrastructure, such as the lack of Closed Circuit Television (CCTV) cameras that are able to monitor speed (speed radar), check points and vehicle license plate recognition (ANPR) at every intersection that implements the Electronic Traffic Law Enforcement (E-TLE) system. Keywords: Implementation, Electronic Traffic Law, Traffic.